Analisis Faktor Penentu Kompetensi Berbasis Karakteristik di Hotel Novotel Karawang - Sofiati (Media Wisata, 2021)
CHARACTERISTIC-BASED COMPETENCY DETERMINANT ANALYSIS IN THE NOVOTEL HOTEL KARAWANG. This study aims to determine the effect of characteristic-based competency in the Novotel Hotel Karawang environment. The sample of this study was 70. Data were collected using a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple regression. The results showed that part there was a significant effect between skills on employee competencies, there was a significant effect between training towards on employee competencies, there was a significant effect between attitudes towards employee competencies, and there was a significant effect between motivation on hotel employee competencies Novotel in karawang. Together, the skills, training, attitude, and motivation factors have a significant influence on the competency of Novotel Hotel employees in Karawang and motivation has the most the dominant influence on the competency of Novotel Hotel employees in Karawang